KEMAMPUAN PEMODELAN MATEMATIKA DALAM REALISTIC MATHEMATICS EDUCATION (RME) - Pitriani Pitriani (Department of Mathematics Education, Universitas Kuningan, 2016)
Mathematical modeling ability: the ability of students in translating a real problem in everyday life sentence into mathematics (mathematical models). Realistic Mathematics Education (RME) is a math learning approach that starts from things that are 'real' for students or contexts easily imagined by students, then represented in the form of formal mathematics through mathematical processes. Learning to use RME to be intensified to remember that this learning can improve students' mathematical modeling ability. By having a good modeling ability so students can complete mathematical problems very well too.Keywords: Realistic Mathematics Education (RME), Mathematical Modeling Ability